Discharge planning for acute coronary syndrome patients in a tertiary hospital: a best practice implementation project. (July 2015) - Lu, Minmin; Tang, Jun; Wu, Jianjin; Yang, Jie; Yu, Jiangyue
Executive summary : Background : Acute coronary syndromes threaten the lives of patients, and pose a high risk for morbidity and mortality despite advances in treatment. Evidence highlights that effective discharge planning is associated with long‐term prognosis of patients. Objectives : The aim of this project was to improve local practice in discharge planning for acute coronary syndrome patients in Huadong Hospital, Shanghai. Methods : Five criteria identified by the Joanna Briggs Institute (JBI) were used to conduct an audit in the Cardiovascular Ward and Coronary Care Unit of Huadong Hospital, Shanghai. Forty‐two nurses and 65 patients were involved. The JBI Practical Application of Clinical Evidence System (JBI‐PACES) and Getting Research into Practice (GRIP) audit tools for promoting change in health practice were used to ascertain compliance with the criteria before and after the implementation of best practice. The program included three phases and was conducted over five months. Results : The project showed that the compliance rates of in‐house education, advice on lifestyle changes, education on discharge medication and left ventricular assessment reached 100%. Psychological screening also attained 97% compliance. There were improvements in the compliance rates of four criteria from 38% to 100%, excluding inhouse education which was already 100% compliant. Conclusions : The project achieved significant improvements in establishing evidence‐based practice of discharge planning for acute coronary syndrome patients in the Cardiovascular Ward and Coronary Care Unit. Strategies for sustaining best practice will continue to be developed in the future.